The internal efficiency and external productivity of the AB-HRM program of DLSU-College of St. Benilde - Garcia, Libertad P. (Animo Repository, 2004)
This study intended to assess the internal efficiency and the external productivity of the Bachelor of Arts in Human Resource Management Program of the De La Salle University-College of St. Benilde using the a systems-based approach of input-process-output-outcome model. From the result of the assessment, the study also hoped to propose a new framework of internal efficiency and external productivity. The study was undertaken using multiple approach of data gathering. Data were gathered from documents, interviews, observations and the use of four sets of survey forms. The survey forms were distributed to graduates, their immediate supervisors, the senior or graduating students and the faculty members of the program. Two levels of analysis, both quantitative and qualitative, were employed in analyzing the problem and in coming up with a new framework of internal efficiency and external productivity. Data from the total population comprised the first level of analysis while the other level consisted of data from the sample group. The AB-HRM program is not quite internally efficient indexed in terms of its cohort survival rate, graduation rate, dropout rate, enrollment trend, and number of terms spent in the program. However, it is internally efficient with the school related variables as indices for efficiency. The AB-HRM Program on the other hand, is externally productive measured in terms of the graduates' employment destination but not in terms of the graduates' involvement in community works after college. Summarizing the results in a nutshell, the new framework shows that among the internal efficiency variables, college GPA followed by the number of terms in the program appear to be more associated with the program's external productivity as seen from the different analysis made. These two variables were on the other hand, influenced by the graduates' age and gender. The AB-HRM program on the other hand, is externally productive as seen in the job search time, job satisfaction, attributes of the graduates and overall job performance.